PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PABRIK TAHU CV. MAKMUR DI PEKANBARU - Kurniawan, Teuku Reza; Viska, Ayu (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
The purpose of this study was to determine the effect of product quality on consumer satisfaction for Samsung smartphones at Justone Ponsel Pekanbaru. The research method used is quantitative research. The sampling technique used incidental sampling, with samples taken using the Slovin formula as many as 89 people. Findings Based on the partial test (test) it is known that there is a significant and positive effect between product quality variables on consumer satisfaction. It was also found that product quality contributed 51.6% to consumer satisfaction while 48.4% was determined by other variables not included in this study